Tappe e percorsi della dialettica hegeliana: la Rivoluzione d’ottobre e il pensiero di Hegel - Sgro', Giovanni (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2023)
The purpose of this paper is to review the studies contained in a recent volume devoted to the influence of Hegel’s thought on Russian philosophy and, indirectly, on the philosophical and political foundations of the October Revolution, dwelling also on Soviet philosophy and its comparison with the interpretation of Hegel offered by some representatives of Western Marxism. Hegel; Hegelian philosophy; Russian philosophy; Soviet philosophy; Western Marxism.